Hardware-aware Database Systems: A New Era for Database Technology is Coming - Vision Paper - Brayner, Angelo; Monteiro Filho, José Maria (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2016: Anais do XXXI Simpósio Brasileiro de Bancos de DadosDO - 10.5753/sbbd.2016.24326, 2016)
A new era of computers with solid state memory (SSDs) chips providing petabytes of storage area is coming. Nonetheless database systems (DBSs) were designed presupposing that databases are persisted in hard disk drives (HDDs) for storing databases. Over the years, DBS components have been optimized based on performance characteristics of HDDs. Simply replacing HDDs by faster SSDs may not fully exploit the capabilities of SSDs. In this paper, we present and defend the idea of hardware-aware database systems in order to make database systems able to fully exploit the advantages provided by new hardware, such as solid state memories.